AMP-activated protein kinase mediates glycolysis in post-mortem breast muscle of broilers. Issue 1 (31st December 2022) - Ruixia, Lan; Wei, Linlin; Wang, Yuchen; Wu, Fan
Abstract: The aim of this study was to confirm the role of AMP-activated protein kinase (AMPK) in the regulation of post-mortem breast muscle glycolysis in the broiler, we evaluated the effects of intraperitoneal injection of the specific AMPK activator (5-aminoimidazole-4-carboxamide ribonucleoside, AICAR) and inhibitor (6-[4-(2-piperidin-1-yl-ethoxy)-phenyl]-3-pyridin-4-yl-pyrazolo[1, 5-a] pyrimidine, Compound C) on AMPK phosphorylation (p-AMPK) level, meat quality, glycolytic metabolites and glycolytic enzymes activities in post-mortem breast muscle of broilers. Compared to the CON group, intraperitoneal injection of AIRCR increased p-AMPK level, glycolytic enzyme activities and lactate content in post-mortem breast muscle, increased lightness ( L* ) and drip loss, but decreased pH45min and pH24h . However, intraperitoneal injection of Compound C, decreased p-AMPK level, glycolytic enzyme activities, glucose-6-phosphate and lactate content in post-mortem breast muscle, and increased pH24h . Based on these results, we conclude that AMPK played a vital role in regulating post-mortem glycolysis in the breast muscle of broilers. HIGHLIGHTS: Injection of AIRCR promoting muscle glycolysis. Injection of Compound C alleviating muscle glycolysis. AMPK played a vital role in regulating post-mortem muscle glycolysis.